A Test Strategy for Discriminating Between Autocorrelation and Misspecification in Regression Analysis - Thursby, Jerry G. (The Review of Economics and Statistics, 1981)
Jerry G. Thursby, A Test Strategy for Discriminating Between Autocorrelation and Misspecification in Regression Analysis, The Review of Economics and Statistics, Vol. 63, No. 1 (Feb., 1981), pp. 117-123